An assessment of the physical factors that influence reading habit among adult group in suburban area of Kuala Lumpur, Malaysia - Sulaiman, Nurul Syafinaz; Ibrahim, Mansor; Hashim, Khairusy Syakirin Has-Yun; Jasmani, Ismail; Md. Saad, Rahimi (American Scientific Publishers, 2017)
Lacking statistic on reading habit among Malaysian, right location in relation to reading preference in the built environment, less attractive of reading programs and deficiency of reading persuasions among citizen are some of the key issues in Malaysian literacy. The paper assesses the reading habits of the adult group in relation to the built environment. Self-completed questionnaire surveys were conducted among adult readers age between 30–70 years old. A sample of 150 respondents was taken from Kampung Sungai Chinchin, Kampung Simpang Tiga and Kampung Tengah Gombak, a suburb of Kuala Lumpur. Based on the analyzes, the majority of the respondents preferred the informal and leisure reading environment. Two-thirds of the respondents rate good views and positive feedback on the idea of an attractive reading place. About half of the respondents strongly agreed that reading would be more efficient and enjoyable in the existence of facilities that supported an informal reading environment. For instance, the internet services provided in the reading area may help readers to access varieties of their preferred reading materials. The respondents agreed on the concept of a reading kiosk in the open air of the park environment positively. This situation may inspire and cultivate the culture of reading habit among the adults as it offers closer to nature and makes the readers feel more relaxed and comfortable. Hence, this research can be a yardstick for a better understanding of the reading habit and attitude of Malaysian, especially among the adult group.